Ambient intelligence environments for accessing building information: A healthcare facility management scenario. Issue 3 (2014) - ,; ,; ,; ,
Abstract : Purpose – Healthcare facility managers work in complex and dynamic environments where critical decisions are constantly made. Providing them with enhanced decision support systems would result in a positive impact on the productivity and success of the projects they undertake, as well as the sustainability of critical healthcare infrastructure. The purpose of this paper is to propose a conceptual ambient intelligent environment for enhancing the decision‐making process of the facility managers. This low‐cost data‐rich environment would use building information modeling (BIM) and mobile augmented reality (MAR) as technological bases for the natural human‐computer interfaces and aerial drones as technological tools.Design/methodology/approach – This paper presents a scenario for the integration of augmented reality (AR) and building information modeling (BIM) to build an ambient intelligent (AmI) environment for facility managers where mobile, natural, user interfaces would provide the users with required data to facilitate their critical decision‐making process. The technological requirements for having such an intelligent environment are also discussed.Findings – The proposed BIM‐MAR‐based approach is capable of enhancing maintenance related practices for facility managers who are mobile to integrate with their facilities' intelligent environment. This approach is also capable of providing a collaborative environment in which different stakeholders, across geographically distributed areas, could work together to solve facility management tasks.Originality/value – In this paper ambient intelligence will be considered for the first time in the area of healthcare facility management practices to provide facility managers with an intelligent BIM‐based environment to access facility information and consequently enhance their decision‐making process.